Efficacy of estriol in inhibiting epithelial proliferation in mammary fi broadenoma: randomized clinical trial - Estevão, Rodrigo Augusto Fernandes; Baracat, Edmund Chada; Logullo, Ângela Flávia; Oshima, Celina Tizuko Fujiyama; Nazário, Afonso Celso Pinto (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Mammary fibroad- enoma is a disease that affects a large number of women of reproductive age. The aim of this study was to evaluate the proliferative activity of mam- mary fibroadenoma through expression of Ki-67 and c-myc antigens, following administration of oral contraceptive with or without estriol. DESIGN AND SETTING: Placebo-controlled double-blind randomized clinical trial in the Mas- tology Sector of the Department of Gynecology, Universidade Federal de São Paulo. METHODS: Thirty-three fibroadenoma patients were studied. Ten women (group 1) took an oral contraceptive constituted by levonorgestrel and ethinyl estradiol together with placebo manufac- tured in the same capsule for four consecutive cycles with a seven-day interval between them. The other 23 patients (group 2) took the same oral contraceptive together with estriol, which was put into the same capsule and used in the same way as among the group 1 patients. After four cycles, the nodules were surgically removed and sent for immunohistochemical analysis of Ki-67 and c-myc expression. RESULTS: The Ki-67 and c-myc analysis did not reveal any significant differences between the study groups. The values were 9.16 and 10.54 for group 1 and 10.86 and 17.03 for group 2, respectively. There was a tendency towards higher expression of antigens in group 2. CONCLUSION: Our results showed that there was no significant statistical difference in Ki-67 and c-myc expression between our study groups, but only a tendency towards higher expression among users of oral contraceptives containing estriol.